Diabetes self-management education on the sustainability of metabolic control in type 2 diabetes patients: Diabetes share care program in Taiwan - Ying-Chuen Lai; Yi-Shuan Chen; Yi-Der Jiang; Chiou-Shiang Wang; I-Ching Wang; Hsiu-Fen Huang; Hui-Yu Peng; Hui-Chuen Chen; Tien-Jyun Chang; Lee-Ming Chuang (Journal of the Formosan Medical Association, 2024)
Background: Diabetes self-management education (DSME) improves glycemic and metabolic control. However, the frequency, duration and sustainability of DSME for improving metabolic control have not been well studied. Methods: The Diabetes Share Care Program (DSCP) stage 1 provided DSME every 3 months. If participants entering DSCP stage 1 ≥ 2 years and HbA1c < 7%, they can be transferred to stage 2 (DSME frequency: once a year). Three-to-one matching between DSCP stage 1 and stage 2 groups based on the propensity score method to match the two groups in terms of HbA1c and diabetes duration. We identified 311 people living with type 2 diabetes in DSCP stage 1 and 86 in stage 2 and evaluated their metabolic control and healthy behaviors annually for 5 years. Results: In the first year, HbA1c in the DSCP stage 2 group was significantly lower than that in the stage 1 group. In the first and the fifth years, the percentage of patients achieving HbA1c < 7% was significantly higher in the DSCP stage 2 group than the stage 1 group. There was no significant difference in other metabolic parameters between the two groups during the 5-year follow-up. Self-monitoring of blood glucose (SMBG) frequency was associated with a reduced HbA1c after 5 years (95% CI: −0.0665 to −0.0004). Conclusion: We demonstrated sustainable effects of at least 2-year DSME on achieving better glycemic control for at least 1 year. SMBG contributed to improved glycemic control. The results may be applied to the reimbursement strategy in diabetes education.